2017
DOI: 10.12691/jmdv-5-1-2
|View full text |Cite
|
Sign up to set email alerts
|

Active Stiffness Method for High Cycle Fatigue Mitigation using Topical Thin Foil Shape Memory Alloy

Abstract: The strong need for high cycle fatigue mitigation has resulted in numerous techniques resulting in added weight, increased operational costs, and lower performance. The experimental investigation presented was a foundational effort towards mitigating HCF through the use of shape memory alloy in a composite system. The research objective was to quantify changes in eigenvalue, eigenvector, and amplitude of a vibrating cantilever beam with a thin SMA topical treatment; as quantified during SMA phase transformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…An experimental study by Nakshatharan [24] using SMA wire applied externally to a clamped-free beam with a constant excitation frequency confirmed that beam tip amplitude reduction of approximately 60% can be achieved in first bending mode. The introduction of the shape memory effect, whereby the shape memory alloy material acts as both a damper and a means of variable stiffness have been confirmed for HCF mitigation [16,17,18,19] using thin sheet metal SMA topically adhered onto a clamped-free beam. This study highlights an amplitude reduction of 92% in the second bending mode with constant excitation frequency.…”
Section: Sma Vibration Controlmentioning
confidence: 93%
“…An experimental study by Nakshatharan [24] using SMA wire applied externally to a clamped-free beam with a constant excitation frequency confirmed that beam tip amplitude reduction of approximately 60% can be achieved in first bending mode. The introduction of the shape memory effect, whereby the shape memory alloy material acts as both a damper and a means of variable stiffness have been confirmed for HCF mitigation [16,17,18,19] using thin sheet metal SMA topically adhered onto a clamped-free beam. This study highlights an amplitude reduction of 92% in the second bending mode with constant excitation frequency.…”
Section: Sma Vibration Controlmentioning
confidence: 93%
“…To initiate the stiffness modulation, RFD employs piezoelectric materials due to their rapid response times. Researchers have also employed shape memory alloys to initiate this variablestiffness effect that, although offering larger potential differences between available stiffness states, appear limited by their slow response times when considering transient excitations [12,13]. By exploiting this variable-stiffness effect, RFD provides robust performance to any unexpected parameter variations and has the ability to target vibration for a number of resonance crossings, provided the piezoelectric elements remain located in a region of high modal strain.…”
Section: Resonance Frequency Detuningmentioning
confidence: 99%
“…This research effort leverages an extremely large experimental and theoretical base. Test specimens were created and consistent with those used to quantify the eigenvalue, eigenvectors, and amplitude changes in recent studies [1,19,20]. The test specimens consisted of a topical treatment adhered to an aluminum substrate.…”
Section: Test Specimen Designmentioning
confidence: 99%
“…High cycle fatigue (HCF) mitigation requires research into novel materials and techniques to expand the available tools and resources for innovated designs. Recent advances in the use of Shape Memory Alloys (SMA) for controlling the vibration characteristics offer significant potential for HCF mitigation cite [1]. High cycle fatigue, as characterized by high frequencies, low amplitudes, cyclic elastic behavior, and high cycle count, affect a large number of engine components.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation